Digital Transformation of Libraries: Web-based Information System Development with Laravel - Ira Widyastuti; Muh. Hajar Harike; Muh. Nasir Takbir; Abdul Malik; Jayanti Yusmah Sari (Journal of Embedded Systems, Security and Intelligent Systems, 2024)
This research addresses the problem of data and information management efficiency in the Regional Library of North Luwu Regency, which is currently still done manually, causing the process of borrowing and returning books to be slow and error-prone. The purpose of this research is to develop a web-based library information system using the Laravel framework to improve efficiency and user satisfaction. The methods used include requirements analysis, system design, development, testing, and evaluation. The results show that the system is able to provide a fast response with an average time of 120-180 ms and has high scalability. Significant improvements were seen in ease of use, access speed, data security, and operational efficiency. Thus, this Laravel-based information system is effective in improving efficiency and user experience and is able to handle future growth.